Analisis Daya Dukung Tiang Pancang Tunggal Berdasarkan Data NSPT yang Diverifikasi dengan Data SLT pada Proyek Gedung SIG 2 Bogor - Priyadi, Wisia Joko; Muktadir, Redho; Hariati, Feril; Taqwa , Fadhila Muhammad Libasut; Nandiasa, Jantiara Eka (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The foundation structure design for the construction of the SIG-2 Building uses a circular pile foundation with a diameter of 0.60 meters and a depth of 15 meters. Verification of the planned bearing capacity was carried out based on data from 2 (two) NSPT test points and continued by comparing the actual carrying capacity based on Static Loading Test (SLT) data. This research aims to compare the planned bearing capacity with the actual bearing capacity during construction, and settlement occurred. Analysis of bearing capacity calculations was carried out based on NSPT data using the Meyerhoff method, while analysis of actual bearing capacity calculations based on SLT data used the Davisson method, Chin method, and Mazurkeiwich method. Based on research conducted at 2 (two) test points, the average bearing capacity of the pile is 185.99 tons, and the average settlement (Sav) is 47.3 millimeters. The allowable settlement is 60 millimeters. The settlement on tested piles is 14,8 mm and 15,8 mm respectively. The results of the bearing capacity analysis based on actual Static Loading Test (SLT) data with a planned load of 200 tons using the Davisson method, Mazurkeiwich method, and Chin method are 179 tons, 185 tons, and 234,9 tons, respectively. Based on the upper structure loading data obtained from the structural planning report, it is concluded that the bearing capacity of the pile group is still safe and able to withstand the planned load on each column of the building structure, assuming the bearing capacity of a single pile of 179 tons, a total of 61 piles with the allowable bearing capacity of all piles of 10,809.81 tons and the building plan load of 9,066.23 tons.